A design methodology of stand-alone photovoltaic power systems for rural electrification. (15th September 2017) - Ghaib, Karim; Ben-Fares, Fatima-Zahrae
Graphical abstract: Highlights: A method for predicting load demand is presented. A new dimensionless number for characterizing PV performance is introduced. A power management strategy for hybrid energy storage systems is proposed. A model for scaling stand-alone photovoltaic power systems is shown. Results that can be used as benchmarks for designing PV systems are provided. Abstract: A promising way to electrify regions lacked to reliable access to electricity is the employment of stand-alone photovoltaic power systems (SPPSs). Recently, the cost of electricity from such systems has fallen, and it is expected that this tendency will continue in the future. Within this paper, a new design methodology of highly reliable and sustainable SPPSs is presented. The approach consists of the following processes: prediction of the load demand, characterization of the PV performance on site, sizing the SPPS considering different storage technologies, and forming the most effective design. On the other hand, a new dimensionless number will be introduced to characterize the PV performance at a particular location. In order to demonstrate the methodology, an intention to electrify 93 households in a rural community is given as an example. The results show that a SPPS configuration including compressed air energy storage and supercapacitor may be the most effective SPPS design.